Aspek Hukum dan Tanggung Jawab Pers - Murani, Asnawi (FISIP Universitas Atma Jaya Yogyakarta, 2005)
Abstract: Press freedom in Indonesia is not apart from its accountabilities for particular delicts as set forth in Press Act and Criminal Law currently revised in line with the development of era and Indonesian cultures. Accountabilities of the press for delicts include humiliation, slandering, and pornography where such involved parties shall account for. Meanwhile, legal aspects for such involved parties include editor, writer, publisher, printing agency and distributors, with more advantageous legal position compared to the ones of non-press delicts.